The gut microbiota regulates diabetic retinopathy in adult rats - Hou, Jueyu; Lv, Zhongping; Wang, Yujiao; Chen, Danian (Frontiers in Microbiology, 2025)
IntroductionDiabetic retinopathy (DR) is the most common complication of diabetes. Neuronal apoptosis, activated microglia, and microvascular changes are early features of DR. The gut microbiota is critical for the maturation and activation of microglia in the brain, and DR patients exhibit gut dysbiosis. However, the effect of the gut microbiota on retinal microglia under normal or diabetic conditions is still unclear.MethodsType 2 diabetes (T2D) was established in male adult Brown Norway (BN) rats, and they were treated with gavage of broad-spectrum antibiotic (ABX) suspension. Retinal fundus fluorescein angiography was performed to observe the dynamic growth process and leakage of blood vessels. Retro-orbital injection of FITC-Dextran was performed to observe the changes in blood-retinal barriers. After treatment with ABX and diabetes lasting for more than 6 months, 16S RNA sequencing of stool samples was performed to determine changes in the gut microbiome and mass spectrometry was used to analyze metabolome changes. IBA1, IB4, and Brn3 staining were performed on adult rats’ retinal wholemount or sections to observe the changes in microglia, blood vessels and the number of ganglion cells.ResultsLong-term (6 months) T2D caused gut dysbiosis with increased average taxa numbers. We showed that broad-spectrum antibiotics (ABXs) gavage can reduce the average number of gut microbiota taxa and retinal microglia in adult male BN rats with or without T2D. Interestingly, adult male BN rats with T2D for more than 6 months showed a loss of retinal ganglion cells (RGCs) without significant changes in retinal microglia or retinal vascular vessels. However, ABX gavage reduced retinal microglia and alleviated RGC damage in these T2D rats.ConclusionOur data suggests that ABX gavage-induced gut dysbiosis can reduce retinal microglia in adult rats and alleviate RGC loss in long-term T2D rats. Targeting the gut microbiota may be a future therapeutic strategy for DR management.